A history of christianity in Asia, Africa and Latin America (1450-1990) - Koschorke Klaus (Grand Rapids W.B. Eerdmans, 2007)
Taking the three continents in turn, the documents trace chronologically the transfer of Christianity from the beginning of Western colonization through the end of the Cold War. Traditional forms of Christianity in Asia and Africa are not covered. The e
Keywords: Asia -- Church history. Africa -- Church history. Latin America -- Church history